2001
DOI: 10.1002/1529-0131(200106)44:6<1420::aid-art237>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of antigen-induced arthritis in inducible nitric oxide synthase-deficient mice

Abstract: Objective Inhibition of nitric oxide (NO) produced by inducible NO synthase (iNOS) is suggested to be beneficial in experimental arthritis. Although NO is important for the integrity of the microcirculation, the effects of inhibition of iNOS on the synovial microcirculation are not currently known. This study investigated the synovial microcirculation and leukocyte–endothelial cell interactions in iNOS‐deficient mice with antigen‐induced arthritis (AIA) and compared these findings with disease severity. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 36 publications
4
19
0
1
Order By: Relevance
“…Similar results, being controversial discussed in literature so far, have been shown in segmental intestinal ischemia/ reperfusion studies [40], leading to the conclusion of NO having an anti-inflammatory effect, also proved in studies using selective and non-selective NOS inhibition [41].…”
Section: Discussionsupporting
confidence: 81%
“…Similar results, being controversial discussed in literature so far, have been shown in segmental intestinal ischemia/ reperfusion studies [40], leading to the conclusion of NO having an anti-inflammatory effect, also proved in studies using selective and non-selective NOS inhibition [41].…”
Section: Discussionsupporting
confidence: 81%
“…Previously, NO was shown to regulate OC recruitment, formation, function, and survival in a complex, potentially biphasic, and context-dependent fashion in which NO can either stimulate (1,9,29,30,42,43) or suppress (7-13, 17-24, 43) OC formation and bone resorption. In particular, iNOS deficiency or pharmacological inhibition of NO (including by AG or L-NIL) has increased OC formation and/or bone resorption in murine, rat, and avian cell cultures (9, 10 -12, 24); stimulated OC recruitment, development, and function in association with angiogenesis in a chicken egg vascular model (13); decreased bone mass in normal or ovariectomized rats (8,25); worsened bone destruction in arthritis models (26,27); and interfered with normal bone fracture healing (28). Consistent with these studies, our present findings strongly support an inhibitory role (in this case, through a novel autocrine mode of action) for NO in restraining RANKL-induced osteoclastogenesis and bone resorption under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas low levels of NO may support osteoblast bone formation and OC-mediated bone remodeling (both basal and cytokine-induced) (9, 19 -22), high NO levels and NO-generating compounds inhibit OC formation and bone resorption and prevent bone loss, for example, in severe inflammation or estrogen-deficient animals (8, 10 -13, 17-24). Conversely, iNOS deficiency or pharmacological inhibition of NO can accelerate OC formation and bone resorption in vivo and in vitro, decrease normal bone mass, exacerbate bone destruction in arthritis or osteoporosis models, and interfere with normal fracture healing (23,(25)(26)(27)(28). On the other hand, iNOS-derived NO has been found in some studies to mediate bone loss in ovariectomized mice, interleukin-1 (IL-1)-induced OC resorption, and TNF-dependent OC survival (22,29,30).…”
mentioning
confidence: 99%
“…Although iNOS has been implicated in the pathogenesis of certain inflammatory diseases, such as arthritis, SLE and irritable bowel syndrome, 62 a number of studies have demonstrated a protective effect of NO against several conditions characterised by inflammation, such as glomerulonephritis, 63 acute hepatic necrosis, 64 arthritis, 65,66 endotoxaemia 64 and acute lung injury 67 in vivo (reviewed by Clancy and Abramson 62 ). Most studies attribute these effects to the wide range of general anti-inflammatory properties of NO, as reviewed by Granger and Kubes, 9 and are outwith the scope of this review.…”
Section: In Vivo Effects Of No and Its Therapeutic Potentialmentioning
confidence: 99%